Integrating Computational Thinking and Islamic Values in Geometry Learning: Effects on Pre-Service Primary Teachers’ Conceptual Understanding - Lilis Marina Angraini; Dianne Amor Kusuma; Reni Wahyuni; Muchamad Subali Noto; Astri Wahyuni; Putri Wahyuni (Bumi Publikasi Nusantara, 2027)
This study examines the integration of computational thinking and Islamic values in geometry learning for Primary School Teacher Education (PSTE) students. Using a quantitative descriptive approach, the research involved 70 PSTE students at Universitas Islam Riau. Data were collected through tests, observations, and interviews, and analyzed using triangulation to ensure validity. This integration significantly improves students’ conceptual understanding, as reflected in the increase in post-test scores. The one-sample t-test yielded a significance value, confirming a meaningful difference between pre- and post-test results. In addition, students internalized Islamic values such as honesty, cooperation, and spiritual awareness during learning activities. This study responds to the need for educational models that balance cognitive skills and character development. The integration of technology and Islamic principles creates a holistic learning experience, contributing to the development of competent, ethical, and responsible future educators.